Stock Liquidity, Corporate Governance, and Leverage in Indonesia - Rita Juliana; Thayogo Thayogo (Riset: Jurnal Aplikasi Ekonomi Akuntansi dan Bisnis, 2019)
This paper studies the relationship between stock liquidity, corporate governance, and leverage in Indonesia. A sample of 165 Indonesian listed firms in the year 2006-2016 is used. The study results confirm that an increase in stock liquidity and corporate governance decreases the use of leverage. This show that corporate governance and stock liquidity able to decrease the agency cost and the usage of debt. The interaction between stock liquidity and corporate governance shows that corporate governance significantly affects leverage only when the firm is liquid. However, there are different results among different proxies of corporate governance quality.